The Correlation of Knowledge and Attitudes to Passive Smoking Behavior among Public Health Students of Sriwijaya University - Dyah Ambarwati; Prihatini Dini Novitasari; Annisah Biancika Jasmine; Rafiah Maharani Pulungan; Fitri Aulia; Putri Inrian Tari (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: There is no safe level of cigarette smoke, but not everyone can avoid the exposure. Public health students are expected to bring changes to healthy behaviors in the community, including getting the right to have air free from cigarette smoke through various preventive efforts. Therefore, this study aims to identify the behavior of public health students at Universitas Sriwijaya as passive smokers, and its correlation with knowledge and attitudes. Subjects and Method: This was a cross-sectional study conducted at Universitas Sriwijaya, South Sumatera, Indonesia, from February to March 2025. A sample of undergraduate students of Public Health was selected using purposive sampling. The dependent variable was smoking behavior. The independent variables were knowledge and attitude. Data were analyzed using a multiple logistic regression. Results: Passive smoking behavior among college students was influenced by knowledge (b = 0.17; 95% CI = –0.14 to 0.47; p = 0.103) and attitude (b = 0.61; 95% CI = 0.26 to 0.96; p = 0.001). While knowledge showed a positive but not statistically significant association with passive smoking behavior, attitude showed a statistically significant positive association. Conclusion: Passive smoking behavior among college students is influenced by knowledge and attitude. Knowledge and attitude have positive association with passive smoking behavior.